Influence of delta-hexachlorocyclohexane (δ-HCH) to Phytophthora ×alni resistant Alnus glutinosa genotypes - Evaluation of physiological parameters and remediation potential - Košková, Stanislava; Štochlová, Petra; Novotná, Kateřina; Amirbekov, Aday; Hrabák, Pavel (Ecotoxicology and environmental safety, 2022)
Hexachlorocyclohexanes (HCHs) are persistent organochlorine pesticides with the adverse effects on human health and the environment. The effect of delta-isomer of hexachlorocyclohexane (δ-HCH) on germination, growth parameters and physiological parameters was studied in different Alnus glutinosa (L.) Gaertn. progeny of resistant genotypes to pathogen Phytophthora ×alni. Two experiments were performed: a short-term experiment to determine the effect of δ-HCH on total germination (GT), germination energy (GE), speed of germination (SG), shoot length and biomass of seedlings, and a long-term experiment devoted to remediation aspects. In addition, changes in the hormonal system of alders were monitored in both cases. Significant differences were found between the treated and control group in most of the evaluated characteristics. Also, the content of studied phytohormones differs between groups. Furthermore, the obtained results indicate genetically determined variability in response to δ-HCH. Of the six tested, the Březové and Tuřany progeny seem to be suitable candidates for phytoremediation because of the adaptation to stress conditions or high remediation efficiency. The rest of tested progeny seems to be unsuitable due to higher mortality, lower remediation efficiency and higher levels of stress hormones resulting in significant decrease in biomass and plant height. Moreover, results indicate the role of the plant as a remediation accelerator, probably through released exudates, and a positive effect on the soil microbiome as the presence of plants increased the remediation efficiency by 20.85 - 35.89%. The obtained research findings may be helpful in better understanding the processes involved in removing these pesticides from the soil. Further research should be focused on rhizosphere microbiome, mechanism of in-plant isomerization and metabolites identification.
Keywords: Pesticides; Phytophthora ×alni; Phytoremediation; genotyp; HCH; pesticidy; olše; lidé; půda; Phytophthora; Hexachlorocyclohexane; Pesticide; Humans; Alnus glutinosa; Alnus; Genotype; Soil